Cover Image, Volume 7, Issue 4. Issue 4 (August 2017) - Medas, Daniela; Cappai, Giovanna; De Giudici, Giovanni; Piredda, Martina; Podda, Simona
Abstract : The cover image, by Daniela Medas et al., is based on the Original Research Article Accelerated carbonation by cement kiln dust in aqueous slurries: chemical and mineralogical investigation, DOI:10.1002/ghg.1681